Overall SME performance evaluation of IDLC Finance Ltd and their contribution to expand Bangladesh economy - Alam, Nusrat (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2018.